1983
DOI: 10.1111/j.1574-6968.1983.tb00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and chemical characterization of regular arrays in the cell walls of strains of the genus Lactobacillus

Abstract: The presence of regular arrays (RAs) in the cell walls of strains of the genus Lactobacillus was examined by electron microscopy. The RAs were found in 6 species including L. bulgaricus, L. helveticus, L. acidophilus, L. fermentum, L. brevis and L. buchneri. The RAs were composed of a protein with an apparent Mr ranging from about 41000 to 55000, depending on the species upon sodium dodecyl sulfate‐polyacrylamide gel electrophoresis (SDS‐PAGE). The amino acid composition of the RA proteins was shown to be acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 15 publications
3
49
0
Order By: Relevance
“…The disappearance of the outer layer from the isolated cell walls after SDS treatment and the concomitant loss of all protein material showed that the predominant 52 kDa protein was located in this layer and that it was in some way noncovalently associated with the underlying layer. Such a 50 kDa protein had previously been encountered in another L. helveticus strain and negative staining experiments had suggested the possibility of a regular surface arrangement (Masuda & Kawata, 1983). In our case no regular arrangement was detected by negative staining (data not shown).…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…The disappearance of the outer layer from the isolated cell walls after SDS treatment and the concomitant loss of all protein material showed that the predominant 52 kDa protein was located in this layer and that it was in some way noncovalently associated with the underlying layer. Such a 50 kDa protein had previously been encountered in another L. helveticus strain and negative staining experiments had suggested the possibility of a regular surface arrangement (Masuda & Kawata, 1983). In our case no regular arrangement was detected by negative staining (data not shown).…”
Section: Discussionmentioning
confidence: 43%
“…Wall and membrane teichoic acids of L. helveticus were shown to have antigenic properties (Knox & Wicken, 1971). It has also been suggested that the cell wall of L. helveticus ATCC 10797 was composed of two layers with the outer layer presumably containing a predominant protein (Masuda & Kawata, 1983). …”
mentioning
confidence: 99%
“…In many species of lactic acid bacteria, including those of the genus Lactobacillus, the presence of surface-layer proteins [30,31,32] has been found. The gene for the S-layer protein has been sequenced and cloned in Lactobacillus brevis [33], Lactobacillus acidophilus [34], Lactobacillus helveticus [35] and Lactobacillus crispatus [36].…”
Section: Microorganisms With Probiotic Propertiesmentioning
confidence: 99%
“…The S protein is capable of crystallization into a regular structure on the outside of bacteria, the S-layer, which covers the entire cell wall during all stages of growth (for reviews see Beveridge, 1994; Messner & Sleytr, 1992). The S-layer is present on bacteria of several Lactobacilh~ species known to inhabit the gastro-intestinal tract (Johnson et al, 1987; Lortal, 1993;Masuda & Kawata, 1983). Schneitz et a/.…”
Section: Boot and O T H E R Smentioning
confidence: 99%